High dosage of monosodium glutamate causes deficits of the motor coordination and the number of cerebellar Purkinje cells of rats. (November 2015) - Prastiwi, D; Djunaidi, A; Partadiredja, G
Monosodium glutamate (MSG) has been widely used throughout the world as a flavoring agent of food. However, MSG at certain dosages is also thought to cause damage to many organs, including cerebellum. This study aimed at investigating the effects of different doses of MSG on the motor coordination and the number of Purkinje cells of the cerebellum of Wistar rats. A total of 24 male rats aged 4 to 5 weeks were divided into four groups, namely, control (C), T2.5, T3, and T3.5 groups, which received intraperitoneal injection of 0.9% sodium chloride solution, 2.5 mg/g body weight (bw) of MSG, 3.0 mg/g bw of MSG, and 3.5 mg/g bw of MSG, respectively, for 10 consecutive days. The motor coordination of the rats was examined prior and subsequent to the treatment. The number of cerebellar Purkinje cells was estimated using physical fractionator method. It has been found that the administration of MSG at a dosage of 3.5 mg/g bw, but not at lower dosages, caused a significant decrease of motor coordination and the estimated total number of Purkinje cells of rats. There was also a significant correlation between motor coordination and the total number of Purkinje cells.